Transformasi Pembelajaran Sejarah Kebudayaan Islam dalam Mengembangkan Kompetensi Guru Profesional Pada Era Digital di MI/SD - Munawir; Wati, Nuzula Kurnia; Sasikirana, Sanjana Rafa (IBTIDA’, 2025)
The transformation of Islamic Cultural History (IS) learning in Madrasah Ibtidaiyah (MI) and Elementary Schools (SD) has become an urgent need in facing the digital era. This study aims to analyze the supporting and inhibiting factors in the application of digital technology in IS learning and to provide strategic recommendations for the development of teacher competencies in the digital era. The research method used is a qualitative approach with literature studies, referring to the TPACK (Technological Pedagogical Content Knowledge) model and an analysis of the digital education transformation policy from the Ministry of Education and Culture of the Republic of Indonesia. The results of the study indicate that the provision of digital infrastructure, the development of technology-based curriculum, and improving teacher competencies are the main factors supporting the transformation of IS learning. Meanwhile, the obstacles faced include limited access to technology, teacher readiness in utilizing technology, and the development of digital content that is in accordance with student needs. Therefore, support from the government, educational institutions, and the community is needed in providing adequate infrastructure and ongoing training for teachers. Periodic evaluation of the application of technology in IS learning is also important to ensure its effectiveness. With a systematic and collaborative approach, the transformation of IS learning can improve the quality of education and form students who are better prepared to face challenges in the digital era.